Jellybeans - Ommen, Sylvia van. (Berkeley, Calif. : North Atlantic Books, 2006)
Two friends, a rabbit and a cat, speculate about what heaven will be like as they enjoy a visit to the park.
Translated from the Dutch.
Kirkus Starred
Publisher's Weekly
School Library Journal
1.6
K-3.
Keywords: Cats -- Fiction; Friendship -- Fiction; Heaven -- Fiction; Rabbits -- Fiction; Cats -- Fiction; Friendship -- Fiction; Heaven -- Fiction; Rabbits -- Fiction